Analisis Efisiensi Produksi Usahatani Sagu di Provinsi Riau: Pendekatan Stokastik dan Deterministik - Yani, Ida Putri; Djaimi Bakce; Syaiful Hadi (Universitas Medan Area, 2025)
Sago is one of the potential commodities in Indonesia as a food reserve. The main issue with sago production is that it is still managed traditionally, without the application of proper cultivation techniques. Generally, sago farmers in Riau Province do not conduct adequate care and maintenance of sago plants, which affects sago productivity. This study aims to analyze the production efficiency of sago farming in Riau Province. The sampling method used was non-probability sampling with purposive sampling techniques. Data analysis was carried out using a stochastic approach with the Cobb-Douglas production function model. The results of the study show that technically, sago farmers in Riau Province are efficient in labor use but inefficient in utilizing harvest area. Therefore, it is necessary to expand the harvest area and adopt a regular planting distance using an equilateral triangle system to increase the number of clumps per harvest area. Meanwhile, allocative and economic efficiency in sago farming in Riau Province has not been achieved. The relatively small number of plant clumps and the high land prices make harvest area utilization allocatively inefficient. Although labor allocation is technically efficient, it is not efficient in terms of allocation and economics. Labor costs are relatively high; thus, to achieve efficiency, it is necessary to reduce labor cost allocation.